2020
DOI: 10.1002/glia.23930
|View full text |Cite
|
Sign up to set email alerts
|

Novel guanidine compounds inhibit platelet‐derived growth factor receptor alpha transcription and oligodendrocyte precursor cell proliferation

Abstract: Oligodendrocyte precursor cells (OPCs), also known as NG2 cells or polydendrocytes, are distributed widely throughout the developing and mature central nervous system. They remain proliferative throughout life and are an important source of myelinating cells in normal and demyelinating brain as well as a source of glioma, the most common type of primary brain tumor with a poor prognosis. OPC proliferation is dependent on signaling mediated by platelet‐derived growth factor (PDGF) AA binding to its alpha recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Specific miRNAs downregulate PDGFRα (Budde et al, 2010 ; Dugas et al, 2010 ; Zhao et al, 2010 ), but PDGFRα downregulation and cessation of OPC proliferation are not necessarily coupled with OL differentiation. For example, guanidine compounds that repress Pdgfra transcription and OPC proliferation do not stimulate OL differentiation (Medved et al, 2021 ). Activation of Akt (Protein kinase B) and mammalian target of rapamycin (mTOR) is critical for OL differentiation (Bercury et al, 2014 ; Ishii et al, 2019 ), and the effect is mediated by FoxO1 (Wang et al, 2021 ; Figure 1C , NFOL).…”
Section: Dynamic Regulation From Npcs To Myelinationmentioning
confidence: 99%
“…Specific miRNAs downregulate PDGFRα (Budde et al, 2010 ; Dugas et al, 2010 ; Zhao et al, 2010 ), but PDGFRα downregulation and cessation of OPC proliferation are not necessarily coupled with OL differentiation. For example, guanidine compounds that repress Pdgfra transcription and OPC proliferation do not stimulate OL differentiation (Medved et al, 2021 ). Activation of Akt (Protein kinase B) and mammalian target of rapamycin (mTOR) is critical for OL differentiation (Bercury et al, 2014 ; Ishii et al, 2019 ), and the effect is mediated by FoxO1 (Wang et al, 2021 ; Figure 1C , NFOL).…”
Section: Dynamic Regulation From Npcs To Myelinationmentioning
confidence: 99%
“…OLs populations can be replenished from various stem cell sources, such as neural, embryonic, and induced pluripotent stem cells (Czepiel et al 2015). These stem cell sources must reach an oligodendrocyte precursor cells (OPCs) state during differentiation into oligodendrocytes (Sim et al 2006), which have greater proliferation and migration ability than OLs (Medved et al 2020); therefore, OPCs are more suitable for post-transplant survival than OLs, which would also increase the extent of myelination.…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells have nerve regeneration, neuroprotection, and neurotrophic properties [ 3 , 4 ]; therefore, stem cell transplantation is considered one of the most promising treatment methods. Studies have shown that OLs can be differentiated from oligodendrocyte precursor cells (OPCs), and OPCs have greater proliferation and migration ability than OLs [ 5 ]; therefore, OPCs are more suitable for post-transplant survival, which also increases the extent of myelination.…”
Section: Introductionmentioning
confidence: 99%